2018
DOI: 10.1002/bjs.10915
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative oral care and effect on postoperative complications after major cancer surgery

Abstract: Preoperative oral care by a dentist significantly reduced postoperative complications in patients who underwent cancer surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
96
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 44 publications
3
96
1
1
Order By: Relevance
“…Our current ndings are incompatible with previous reports investigating the effectiveness of preoperative oral hygiene care for patients undergoing esophagectomy (10,11,12); evidence of its effectiveness has also been reported by several studies in elds of surgery other than esophagectomy (17,18). The discrepancy might be explained in part due to differences in preoperative intervention methods.…”
Section: Discussioncontrasting
confidence: 99%
“…Our current ndings are incompatible with previous reports investigating the effectiveness of preoperative oral hygiene care for patients undergoing esophagectomy (10,11,12); evidence of its effectiveness has also been reported by several studies in elds of surgery other than esophagectomy (17,18). The discrepancy might be explained in part due to differences in preoperative intervention methods.…”
Section: Discussioncontrasting
confidence: 99%
“…The present study showed that the oral bacteria count significantly increased immediately after heart surgery, especially in intubated patients, but returned to baseline values several days afterwards. Previous reports have shown that perioperative oral health care could decrease the risk of pneumonia and improve prognosis in gastrointestinal cancer and heart surgery cases [2,3,9], as oral bacteria are nosocomial pneumonia-suspected pathogens [1]. Findings from this study support the notion that increased oral bacteria numbers after surgery may be a risk factor for postoperative pneumonia.…”
Section: Discussionsupporting
confidence: 80%
“…For patients at risk of infectious endocarditis (IE), such as those with acquired valvular disease or receiving an artificial heart valve replacement, dental check-ups and treatment are recommended to prevent odontogenic infection, according to IE prevention guidelines [8]. Therefore, dental intervention prior to surgery is important as it has the potential to reduce the risk of postoperative circulatory and respiratory infections in patients receiving heart valve surgery [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, it was observational and did not include a control group without oral healthcare intervention group. Due to several previous reports on the effects of preoperative oral care on reduction of the risk of postoperative pneumonia (Akutsu et al, ; Bergan, Tura, & Lamas, ; Ishimaru et al, ; Shigeishi et al, ), it is ethically and clinically difficult to construct the study protocol without perioperative intervention. Accordingly, preoperative periodontal treatment was performed for all participants in this study.…”
Section: Discussionmentioning
confidence: 99%